Monitoring of soil temperatur on permafrost in natural and anthropogenic disturbed conditions in the Tunkinskaya Depression - N. N. Voropay; M. V. Kiselev; A. A. Cherkashina (Лëд и снег)
The territory of the study is the Tunkinsky intermountain basin (South-Western Baikal region, Republic of Buryatia) which belongs to the area of sporadic (island) distribution of permafrost. Soil temperature controls many biotic and abiotic processes in it, so it is important to monitor the freezing and thawing regimes in peat and mineral soils. The object of the study is coarse-humic cryogenic soils on sandy lacustrine-alluvial sediments. The first site was represented by natural coarse-humic cryogenic soils under spruce forest, while the second site was organized on the area where in 1960s the forest had been destroyed and the soils were ploughed. At the end of XX century, the arable lands were abandoned, and now they are covered with steppe grasses (the long fallow). Both sites are located on the permafrost. The atmospheric-soil measuring complex was used to study the state of both the perennial and seasonal permafrost at these two sites. The soil temperatures were measured in automatic mode with a time interval of 1 hour from July 1, 2013 to June 30, 2017 along the soil profile from the surface down to a depth of 320 cm. Anthropogenic interference on one of the sites resulted in changes in vegetation cover, the soil moisture as well as the morphological structure and granulometric composition of the upper part of the soil layer. This caused changes in the temperature regime of the permafrost and its degradation with lowering of its upper limit. The soil on the long fallow is better warmed up and cools down faster than it takes place under the spruce forest. As a result of this, the maximum annual temperature on the surface here is higher by 10 °C, while at a depth of 320 cm – by 5 °C, and the minimum annual temperature on the surface is lower by 7 °C, while at a depth of 320 cm – by 1 °C. On the anthropogenically disturbed area, the warm period (at the soil temperature above 0 °C) on the surface is, on the average, by 22 days longer than on the natural lot. These differences are observed at all depths. As a result, the perennial permafrost is retained under the spruce forest below 130 cm throughout the year (soil temperature −0.2 ÷ −0.9 °C), while on the fallow the zero isotherm during seasonal thawing falls much deeper 320 cm, and the soil in the layer of 240–320 cm warms up to 2–5 °C.